Efficacy of atomoxetine and oxybutynin in the treatment of pediatric obstructive sleep apnea, a three case report - Larramona Carrera, Helena (Frontiers in Sleep, 2025)
Persistent severe obstructive sleep apnea (OSA) after adenotonsillectomy (AT) is not uncommon in children with genetic syndromes and/or obesity. Although continuous positive airway pressure (CPAP) is the standard treatment, adherence in pediatric patients is often low, limiting its effectiveness. We report three cases of children with persistent OSA and failure to continue CPAP therapy, in whom an alternative pharmacological approach was explored. In agreement with their families, a 4-week trial of combined atomoxetine and oxybutynin was initiated. Of note, the first patient was concurrently treated with lisdexamfetamine for attention deficit hyperactivity disorder, while the second had morbid obesity under treatment with liraglutide. Both patients demonstrated a great improvement in their apnea-hypopnea index (AHI), with reductions >50% measured by polysomnography. The combination therapy was well tolerated, with no significant adverse effects or interactions with ongoing medications. The third patient did not adhere to the drug therapy, and the effect of a single night of treatment before the follow-up polysomnography was evaluated, showing no change in AHI. These cases suggest a potential role for atomoxetine and oxybutynin as alternative therapeutic options for pediatric OSA in complex scenarios where severe OSA persists despite AT and failed CPAP therapy, warranting further evaluation in large pediatric clinical trials. Nevertheless, the final case underscores that even pharmacological treatments, although seemingly straightforward to administer, may encounter adherence challenges.